2015
DOI: 10.1007/s10689-015-9852-6
|View full text |Cite
|
Sign up to set email alerts
|

Non-genetic health professionals’ attitude towards, knowledge of and skills in discussing and ordering genetic testing for hereditary cancer

Abstract: Non-genetic health professionals (NGHPs) have insufficient knowledge of cancer genetics, express educational needs and are unprepared to counsel their patients regarding their genetic test results. So far, it is unclear how NGHPs perceive their own communication skills. This study was undertaken to gain insight in their perceptions, attitudes and knowledge. Two publically accessible databases were used to invite NGHPs providing cancer genetic services to complete a questionnaire. The survey assessed: sociodemo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
44
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(49 citation statements)
references
References 32 publications
4
44
0
1
Order By: Relevance
“…The response rate for this survey was similar to previous physician knowledge studies (Cohn et al, ; Douma et al, ). There was no difference in response rates between the Ob/Gyn and Family Medicine groups.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…The response rate for this survey was similar to previous physician knowledge studies (Cohn et al, ; Douma et al, ). There was no difference in response rates between the Ob/Gyn and Family Medicine groups.…”
Section: Discussionsupporting
confidence: 82%
“…Published studies surveying non‐genetic health professionals showed significant gaps and a wide range of knowledge regarding BRCA1/2 genetic testing and management among both specialists and primary care providers (Dhar et al, ; Pal et al, ; Teng & Spigelman, ; Wideroff et al, ). Even among non‐genetic health professionals who reported routinely providing cancer genetic services, there remained a need to continue education (Beitsch & Whitworth, ; Douma, Smets, & Allain, ).…”
Section: Introductionmentioning
confidence: 99%
“…With the push to incorporate personalized genomics into general practice, an understanding of genetics continues to be increasingly important in healthcare (Sperber et al 2017). However, previous studies have shown that medical students and non-genetics physicians may not have the genetics knowledge that is considered important for healthcare providers, nor are they comfortable ordering genetic tests (Baars et al 2005;Douma et al 2015;Marzuillo et al 2013;Salm et al 2014). This raises concerns about the quality of patient care that may be provided by nongenetics professionals (Bonadies et al 2014;Cragun et al 2014;Vadaparampil et al 2014).…”
Section: Implications For Practice and Researchmentioning
confidence: 99%
“…21 Challenges with managing the results from genomic sequencing tests have also been examined, especially for primary care or specialist providers who have limited training and experience in clinical genetics. 22,23 Educational programs exist for non-genetics health professionals and have been shown to be beneficial in enhancing knowledge, self-efficacy, and confidence, among other outcomes. 24 Yet, these educational programs might not significantly change practice.…”
Section: Introductionmentioning
confidence: 99%